2022
DOI: 10.1037/dev0001297
|View full text |Cite
|
Sign up to set email alerts
|

The role of household chaos on levels and trajectories of socioemotional behavior in the second year.

Abstract: The second year of life is a time of formative developmental change as basic behavioral systems undergo rapid integration and expansion. This study examined the developmental trajectories of socialemotional (SoE) outcomes and the effects of infant sex and household chaos (HC) on the development of SoE outcomes across the second year of life. The participating families (N = 143) were ethnically homogenous (88% Caucasian) but economically diverse (31% low-to-very-low income). Mothers reported on their children's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(132 reference statements)
1
2
0
Order By: Relevance
“…Additionally, the current study was underpowered to evaluate sex differences. Nonetheless, consistent with past research, positive parenting behaviors and home environments in early childhood were associated with fewer externalizing behaviors in children in the current study (Anderson & Goodnight, 2022;Boeldt et al, 2012;Chimed-Ochir et al, 2022;Hentges et al, 2018;Pinquart, 2017;Shaw et al, 1998;Trentacosta & Shaw, 2008). These results align with theoretical models that state that early caregiving environment is critical to the expression of these externalizing types of behavior problems in children (Cummings & Miller-Graff, 2015;Mikulincer & Shaver, 2019;Patterson, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the current study was underpowered to evaluate sex differences. Nonetheless, consistent with past research, positive parenting behaviors and home environments in early childhood were associated with fewer externalizing behaviors in children in the current study (Anderson & Goodnight, 2022;Boeldt et al, 2012;Chimed-Ochir et al, 2022;Hentges et al, 2018;Pinquart, 2017;Shaw et al, 1998;Trentacosta & Shaw, 2008). These results align with theoretical models that state that early caregiving environment is critical to the expression of these externalizing types of behavior problems in children (Cummings & Miller-Graff, 2015;Mikulincer & Shaver, 2019;Patterson, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, sensitive parenting behaviors and an emotionally supportive and cognitively stimulating home environment in early childhood may alter neurodevelopment and physiological functioning in a manner that mitigates risk for internalizing following prenatal stress. Second, a supportive and responsive caregiving environment in the first years of life may help to foster secure attachment bonds, emotional security, and emotion regulation even in contexts of risk (Chimed-Ochir et al, 2022;Crespo et al, 2017;Glynn et al, 2021). For example, according to Emotional Security Theory, a family environment that is warm and responsive may promote feelings of emotional safety and emotion regulation skills that in turn prevent internalizing symptoms (Cummings & Miller-Graff, 2015;Maccoby, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Children’s social withdrawal behavior determines whether individuals have communication motivation which affects the development of their social skills in social interaction ( Brei et al, 2014 ; Blume et al, 2021 ). Previous studies revealed that household chaos will affect the development of individual thinking, language, and social communication ability ( Vernon-Feagans et al, 2016 ; Chimed-Ochir et al, 2022 ). Influencing factors of family chaos and psychological mechanisms have always been a concern by researchers.…”
Section: Introductionmentioning
confidence: 99%